Single-number values versus subjective judgment of airborne sound insulation in dwellings. Issue 1 (March 2023) - Rauscher, Thomas; Neubauer, Reinhard O.; Zaglauer, Maria; Leistner, Philip
There is a long history of adapting airborne sound insulation in buildings to the actual needs. A first pan-European work was published with COST Action TU0901: Integrating and Harmonizing Sound Insulation Aspects in Sustainable Urban Housing Constructions in which the differences between the sound insulation measure and the standard sound level difference were documented. Furthermore, ISO 16283-1: Field measurement of sound insulation in buildings and of building elements—Part 1: Airborne sound insulation states: Compared to DnT, R' has a weaker connection to the subjective impression of airborne sound insulation. To investigate this relationship a simplified listening test and a computer-simulated variation studies of a synthesized airborne sound insulation were carried out. A test sound was generated from a speech, a music, and a noise signal, each of which was filtered by six frequency responses of solid structures. In a paired comparison task, 16 participants judged the loudness of the resulting 18 sounds. The results of the listening test show that perceived loudness is significantly correlated to the single number quantity DnT, w but less to the single number quantity R'w . This finding was confirmed across all signal types. Thus, the results confirm the statement in ISO 16283-1, that the single number quantity DnT, w has a stronger connection to the subjective impression of airborne sound insulation as the quantity R'w .